Teaching English to Sanitary Students - Akram Hashemi (Randwick International of Education and Linguistics Science Journal, 2021)
English Specific Course books should fulfill the real needs and objectives of the learners of special fields, actually in Corona arena. This study enjoyed a mixed method that evaluated the public textbook for the professional health, taught at Medical Branch. Two standard questionnaires administered in this research after piloting based on a Likert-scale evaluation checklist and Davoodi’s needs analysis questionnaire followed by an interview from the students. Data was analyzed via SPSS software version 22.0 and the findings revealed that the text book entitled “English for professional health students” was suitable for the related course from the students’ attitude, but it did not meet the students’ actual needs. Moreover, it provided valuable implications for students, teachers, syllabus developers and administrators.